Gender Gaps In Financial Literacy: A Study Of English Literature Students - Simbolon, Amelia Agnes; Sianipar, Stefanny Romauli; Hartati, Rita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Financial literacy encompasses the knowledge, skills, and confidence to make informed financial decisions and is critical to individual and societal well-being. The gender gap in financial literacy is widespread and persistent. Using Chen and Volpe’s (1998) framework, this study aims to examine the level of financial literacy of English Literature study program students from a gender perspective. This study used a quantitative descriptive method, with data collected from 77 seventh-semester students through a validated questionnaire. The results showed an overall moderate level of financial literacy, with an average correct answer rate of 73.2%. Personal financial planning emerged as the most vital domain, while debt management was the weakest domain. Analysis from a gender perspective showed that female students had a higher average score (73.94%) than male students (69.8%), although there was more significant variability in scores among female students. These results suggest that female students generally have better financial literacy. Women are more engaged in financial literacy learning when the material is relevant to their personal or social needs, such as household budget planning and future financial security.